Antibacterial Activity Test of Roll on Deodorant Extract Ethanol Tamarind Seed Coat - Rahim, Abdul Rahim; Salmiah; Ihsan, Ersi Arviana (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2023)
Introduction: Armpit odor is one of the problems caused by bacteria, one of which is Staphylococcus aureus. The rind of the tamarind seed contains tannins and flavonoids that function as antibacterial. Aims: The purpose of this study was to formulate the ethanolic extract of tamarind seed coat into roll-on deodorant preparations and to determine the zone of inhibition from variations in the concentration of the extract. Methods: The method used is the well diffusion method and the data obtained are then analyzed using Statistical Product and Service solution (SPSS). The level of confidence used is 95% to see the significance of each evaluation of the preparation. Result: The results showed that the roll on deodorant preparation of ethanol extract of tamarind seed coat did not meet the requirements for good dispersibility, adhesion and viscosity for topical preparations in general and emulsion preparations. The pH of the preparation met the axillary skin pH he standard for topical preparations. The roll-on deodorant preparation of ethanol extract of tamarind seed cultivars was effective in inhibiting the growth of Staphylococcus aureus bacteria. Conclusion: The results of inhibition zone 3 formulations containing extracts were in the strong category and the value increased with increasing concentration of tamarind seed coat extract in the deodorant preparation.